The Steps of Daelyin’s Decision to Commit Suicide as an Escape Way in Julie Anne Peters’ By The Time You Read This, I’ll Be Dead - Tissa Risanto; Hilaria Dewi Hapsari (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2020)
This study analyzes the steps of Daelyn’s decision to commit suicide as an escape way in Julia Anne Peters’ By The Time You Read This I’ll Be Dead. The objective of this study is to find out the steps of Daelyn’s decision to commit suicide as an escape way. To answer the problem, the writers apply a psychoanalytic theory from Roy Baumeister named escape theory . The writers uses library research as the method to collect the data. The result of the study reveals that Daelyn gets through six steps until she decides to commit suicide as an escape way. Those six steps are Daelyn experiences bad conditions in her current life as the result of her painful experiences, Daelyn makes negative assumptions about herself, Daelyn realizes that her life is worse than other people as the result of comparing herself with others’ standards, Daelyn experiences the negative effect as the result of self-comparison, Daelyn is in a mental stage where she does not feel any emotions and senses in her life, and finally, Daelyn decides to commit suicide.